ESTUDO DA OCORRÊNCIA, ASPECTOS COMPORTAMENTAIS E BIOLÓGICOS DE BOTHYNUS STRIATELLUS (FAIRMAIRE, 1878) (COLEOPTERA: SCARABAEIDAE) - Amaro, Ricardo Aparecido; Rodrigues, Sérgio Roberto (ANAIS DO ENIC, 2018)
-